Developing Principal Leadership through Experiential Learnings - Tanjung, Bahdin Nur; Elfrianto, Elfrianto; Pulungan, Lilik Hidayat; Nasution, Mutiara Akbar (Lembaga Riset Mutiara Akbar, 2025)
This study aims to identify and analyze how principal leadership development occurs through experiential learning. This study uses a literature review method to examine various literatures related to the concept of principal leadership and experiential learning. In the context of ever-evolving education, principals face complex challenges, ranging from policy changes to technology integration. The results of the study indicate that structured reflection, mentoring, practice-based training, and institutional support are key elements in leadership development. Reflection allows principals to evaluate decisions and actions in depth, while mentoring provides direct guidance from more experienced leaders to overcome real challenges. Practice-based training, such as leadership simulations and case studies, helps principals improve their skills in making strategic decisions. In addition, institutional support plays an important role by providing resources, supportive policies, and a conducive environment for continuous learning. This article recommends a holistic approach that integrates these elements to create an effective and relevant leadership development strategy in various educational contexts. With a systematic experience-based approach, principals are expected to be able to become adaptive, innovative, and effective learning leaders in facing the challenges of 21st century education.